A rua, o poeta e o romantismo: a produção literária de Sales Barbosa - Almeida, Cíntia Portugal de (2016)
In this dissertation, we present Francisco de Sales Barbosa (1862-1888), the poet of the street, law school student, the "Paraíba", member of "Clube do Cupins", abolitionist, journalist, public prosecutor, born in the village of Arraial Sant'Anna Fair, today City of Feira de Santana, State of Bahia, Brazil. It is and was in his time, an influential personality in the cultural and political local scene. It is involved with the French literature, German, Brazilian, backlands, was singer of disallowance. Appropriated the poetry recited and heard in the square, made the genre a means to express their struggles and passions in the ideological field. Shared laughter, pain captive, dreams of freedom and justice, backcountry scenery the French fashion, scented by the winds of the alleys. Journalist engaged in social causes, though not recognized as such. He was founder and publicist of some journals of the city, true, rare and scattered. Salvador and Recife, at the time, were disseminators of his poetry. Enter a number and another of feirenses periodicals, the mid-nineteenth century, appeared the author of Cavatinas (1885). Through a combative voice, reflective, ironic, highlighted the injustice, the captives and political power. Our research will say that this is the third poet romantic generation. From theoretical studies of memory and identity, based on sources and periodic studies, visualizaremos the living role of the romantic poet of the Middle Street, the Street Sales Barbosa, the voice not heard in the square that echoes in the country today. So with the study we try to rescue the production of Feirense Francis de Sales Barbosa (1862-1888). The research is bibliographical and documentary.